The college application essay - McGinty, Sarah Myers (Boston Marlborough street books, 2015)
"The 25th- anniversary edition of this best-selling guide gives students simple strategies to maximize the opportunity to "tell us about yourself." Updated to reflect the experience college applicants face today, this book provides a clear path to an essay that says, "Pick me!""--
Includes bibliographical references and index.
Keywords: College applications -- United States; Universities and colleges -- United States -- Admission; Exposition (Rhetoric); Essay -- Authorship; STUDY AIDS / College Entrance